Tuberous Sclerosis Complex 1 Regulates dE2F1 Expression during Development and Cooperates with RBF1 to Control Proliferation and Survival. - Hsieh, T.C.; Nicolay, B.N.; Frolov, M.V.; Moon, N.S. (PLoS Genetics, 2010)
Previous studies in Drosophila melanogaster have demonstrated that many tumor suppressor pathways impinge on Rb/E2F to regulate proliferation and survival. Here, we report that Tuberous Sclerosis Complex 1 (TSC1), a well-established tumor suppressor that regulates cell size, is an important regulator of dE2F1 during development. In eye imaginal discs, the loss of tsc1 cooperates with rbf1 mutations to promote ectopic S-phase and cell death. This cooperative effect between tsc1 and rbf1 mutations can be explained, at least in part, by the observation that TSC1 post-transcriptionally regulates dE2F1 expression. Clonal analysis revealed that the protein level of dE2F1 is increased in tsc1 or tsc2 mutant cells and conversely decreased in rheb or dTor mutant cells. Interestingly, while s6k mutations have no effect on dE2F1 expression in the wild-type background, S6k is absolutely required for the increase of dE2F1 expression in tsc2 mutant cells. The canonical TSC/Rheb/Tor/S6k pathway is also an important determinant of dE2F1-dependent cell death, since rheb or s6k mutations suppress the developmentally regulated cell death observed in rbf1 mutant eye discs. Our results provide evidence to suggest that dE2F1 is an important cell cycle regulator that translates the growth-promoting signal downstream of the TSC/Rheb/Tor/S6k pathway.